Comportamiento agronómico de tres variedades de maní (Arachís hipogaea l.) en el cantón Quinsaloma. - Barros Contreras, Jonathan Carlos (2014)
In order to evaluate the agronomic performance of three varieties of groundnut (Arachis hypogaea L.) in the Quinsaloma Canton (79 ° 21 'west longitude, 1 ° 06' South latitude). An investigation was carried using a design in randomized complete block (RCBD) with 4 treatments and 4 replications; using three varieties of peanuts and a control. The results indicate no statistical significance for varieties or repetitions according to the Tukey test at 95% probability, the variety introduced earlier regarding days to flowering with Charapotó value was 26.50 days, as to plant height the highest average, showed the variety Charapotó with 30.50 cm, number of pods per silver, the highest average per plant, which showed the 381 range with 36.20 lNlAP pods, pod length in the highest average was with 3.60 cm variety lNlAP 381, the number of grains per pod variety lNlAP 382 presented the highest average 3.20 grains in weight was determined that lNlAP 380 range with an average 56.31 / g, and the yield per hectare the range 382 to 5194 Kg lNlAP, one can observe that the treatment presented higher costs, revenues, net income, was shown by the variety lNlAP 382, with $ 4,375.25, $ 10,284.14 and $ 5,909.14 respectively Al analyze the cost benefit ratio is observed that the best relationship is also obtained with the INIAP 380, with a value of 1.52, followed by 1.43 INIAP 380, well above the values shown by the variety Charapotó showed a value of 0.67.